Kepatuhan Minum Obat, Luaran Klinis dan Kualitas Hidup Pasien Dislipidemia: Studi Potong - Lintang - Fauziah, Syifa; Syafhan, Nadia Farhanah; Puspitasari, Atika Wahyu; Arrum Kusumawardani, Larasati (Poltekkes Kemenkes Bandung, 2026)
Background: Dyslipidemia is a disease that requires long - term drug therapy. High in medication adherence is necessary to achieve the good clinical outcome and quality of life. Objective: This study aimed to provide medication adherence, clinical outcome, and quality of life in dyslipidemia patients and assess the influencing factors. Methods: This study used a cross - sectional design conducted at Universitas Indonesia Hospital. Morisky Medication Adherance Scale-8 (MMAS-8) questionnaire and EQ-5D-5L questionnaire were used to assess patient’s medication adherence and quality of life. Statistical analysis was carried out using the Chi – Square test with confidence interval of 95%. This study involved 81 dyslipidemia patients in the period from September 15th to October 14th 2025. Results: This study showed that 64.2% of patients had high medication adherence. A total of 88.9% of dyslipidemia patients had controlled total cholesterol levels, and 90.1% had a good quality of life. Gender, age, education, comorbidities, number of medications, and duration of therapy did not affect medication adherence, clinical outcomes, or quality of life among dyslipidemia patients. However, duration of therapy was found to be associated with the quality of life of dyslipidemia patients (p=0.049). Conclusion: Most dyslipidemia patients had high medication adherence, controlled total cholesterol levels, and a good quality of life. Duration of therapy was associated with the quality of life of dyslipidemia patients.